PENERAPAN PEMBELAJARAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR FLIYING SHOOT BOLA TANGAN PADA DI SMA KEMALA BHAYANGKARI KUBU RAYA - Denny, Denny; Purnomo, Edi; Supriatna, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ The problem in this research is whether there is any influence of audio visual learning media on the result of learning fliying shoot handball game on the students of class X A in SMA Kemala Bhayangkari Kubu Raya. The purpose of this study is to determine the effect of audio visual learning media on the results of learning fliying shoot handball game on the students of class X A in SMA Kemala Bhayangkari Kubu Raya. The method used in this research is experimental method with pre-experimental design. population in this study all students of class XA in SMA Kemala Bhayangkari Kubu Raya which amounted to 31 students. In this research to do sample saturation technique or take entire population that is student of class XA in SMA Kemala Bhayangkari Kubu Raya which amounts to 31 student. Data analysis was done by using t-test analysis. Analysis of influence test through t-test application got t-test> tabel or 17.366> 2.042 meaning that hypothesis accepted there is influence of audio visual learning media to result of learning fliying shoot handball game at student of class X A in SMA Kemala Bhayangkari Kubu Raya. Percentage improvement of learning result of basic technique of fliying shoot handball game on X A class students in SMA Kemala Bhayangkari Kubu Raya is 39.19%.Keywords: Audio Visual Media, Flying Shoot Handball